Akuntansi Belis dalam Adat Perkawinan Masyarakat Kabupaten Sikka - Renata Ritarosana Dua Pona; Wilhelmina Mitan; Paulus Libu Lamawitak (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to describe the identification, measurement, presentation and disclosure of belis accounting in the marriage customs of the Watugong Village community. This research data was obtained from interviews, observations, documentation and literature studies regarding the stages of belis in the marriage customs of the Watugong village community. This research produces data that can be used as information and consideration in making decisions regarding accounting. The results of this research: identification in Accounting is said to be relevant because in the buying process economic transactions can be identified; This research shows the process of measuring belis, measured using fair value, which is in accordance with the market price set at that time; The researcher presents a journal description and a summary of profits or losses from both parties, which can be used as reference material for future purchasing processes, documentary evidence and economic considerations.